2018
DOI: 10.1373/clinchem.2017.277517
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of Maternal Neoplasia in Noninvasive Prenatal Testing

Abstract: In a population of pregnant women who submitted a blood sample for cfDNA testing, an abnormal genomic profile not consistent with fetal abnormalities was detected in about 10 out of 100000 cases. A subset of these observations (18 of 43; 41.9%) was attributed to maternal malignant neoplasms. These observational results suggest the need for a controlled trial to evaluate the potential of using cfDNA as an early biomarker of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 31 publications
3
109
2
Order By: Relevance
“…The cancers included four cases of lymphoma, one acute T-cell lymphoblastic leukaemia, one anal cancer, one CRC, and one cancer of neuroendocrine origin, all diagnosed within 39 (mean 16) weeks of the NIPT test. In a similar report, Dharajiya et al [117] identified 0.01% (55/ 450 000) with multiple copy number deviations for the test chromosomes in clinical NIPT. Followup information was available for 43 cases.…”
Section: Universal Screeningmentioning
confidence: 80%
See 1 more Smart Citation
“…The cancers included four cases of lymphoma, one acute T-cell lymphoblastic leukaemia, one anal cancer, one CRC, and one cancer of neuroendocrine origin, all diagnosed within 39 (mean 16) weeks of the NIPT test. In a similar report, Dharajiya et al [117] identified 0.01% (55/ 450 000) with multiple copy number deviations for the test chromosomes in clinical NIPT. Followup information was available for 43 cases.…”
Section: Universal Screeningmentioning
confidence: 80%
“…In a similar report, Dharajiya et al . identified 0.01% (55/450 000) with multiple copy number deviations for the test chromosomes in clinical NIPT. Follow‐up information was available for 43 cases.…”
Section: Can Ctdna Be Used In Cancer Screening Programmes In Defined mentioning
confidence: 99%
“…This is particularly likely when single monosomies or multiple rare aneuploidies, which are typically deemed lethal, are seen in an ongoing pregnancy. In a recent study of more than 450 000 NIPT samples, Dharajiya and coworkers found abnormal genomic profiles with multiple aneuploidies in 55 cases and subsequently confirmed the presence of maternal neoplasia in 40 of the 43 cases available for follow‐up . Interestingly, half of these involved uterine leiomyomas, which are considered to be benign neoplasms .…”
Section: Expanded Non‐invasive Prenatal Testing: Advantages Challengmentioning
confidence: 98%
“…A challenging possibility associated with the finding of rare autosomal aneuploidies by NIPT is that of maternal cancer . This is particularly likely when single monosomies or multiple rare aneuploidies, which are typically deemed lethal, are seen in an ongoing pregnancy.…”
Section: Expanded Non‐invasive Prenatal Testing: Advantages Challengmentioning
confidence: 99%
See 1 more Smart Citation